Causal Relationship Model of Flood Response Behavior - Mongkonsin, Cherdpong; Thiengkamol, Nongnapas; Thiengkamol, Tanarat (Mediterranean Journal of Social Sciences, 2013)
The populations of 2,200 peoples who faced with flood disaster in Mahasarakham Province in 2011. The 401 peoples wereused as sample group. The questionnaire was used as instrument for data collection. LISREL was used for model verification.Considering on structural model confirmatory factors of Environmental Education Principle (EEP) and Community Strength(CoS) were able to explain the variation of endogenous factors of Inspiration for Flood Response (INS) to caused FloodResponse Behavior (FRB) with 87.00 percents. As a result, the equation 1 can be written as following.FRB = 0.99*INS + 0.069*EEP - 1.00*CoS ………………………(1)R2 = 0.75Equation (1) factors that had the most effect to Flood Response Behavior (FRB) was Inspiration for Flood Response (INS) andsubsequences were Environmental Education Principle (EEP) and Community Strength (CoS), these were able to explainedthe variation of Flood Response Behavior (FRB) with 75.00 percents. Moreover, confirmatory factors of EnvironmentalEducation Principle (EEP) and Community Strength (CoS) were able to explain the variation of confirmatory factors ofInspiration for Flood Response (INS) with 93.00 percents. Therefore, the equation can be written as following equation 2.INS = 1.91*CoS - 0.35*EEP ……………………..………..……(2)R2 = 0.93